Food subsidies and cash transfers in Egypt: Evaluating general equilibrium benefits and trade-offs - Breisinger, Clemens; Kassim, Yumna; Kurdi, Sikandra; Randriamamonjy, Josee; Thurlow, James (International Food Policy Research Institute, 2021)
Most Egyptians receive food subsidies, which are the cornerstone of the country’s social protection system. The government recently attempted to reduce subsidies, with limited success, and introduced a cash transfer program targeting the poor. We use a dynamic general equilibrium model of the Egyptian economy to evaluate the growth and distributional impacts of subsidy reforms and cash transfers. We find that the welfare of poor households would be enhanced by a smaller, but better targeted food subsidy program, and that, if the cost savings from reforms are channeled into investment, faster economic growth would eventually outweigh any short-term welfare losses. However, most of the gains from subsidy reforms accrue to nonpoor households. Combining subsidy reforms with cash transfers leads to the largest welfare gains for the poor, while leaving the welfare of nonpoor households largely intact. The latter is crucial to maintaining support for ongoing subsidy reform efforts.